Lateglacial studies in the western valleys of the Italian Julian Alps and in the Koritnica valley - Tintor, Wolfgang (Acta geographica Slovenica, 2014)
Different from the northern valleys of the Italian Julian Alps the bottoms of the western valleys do not contain any late-pleistocene moraines. However, common to all valleys is the large glaciation most probably in the Gschnitz-stage, in which the glaciers reached particularly low locations due to special favourable aspects such as north-exposure, steep and narrow gorges, high shading and considerable snow accumulation. This is also valid for the sidebranches of the Slovenian Koritnica valley which are again directedwest-east. Still younger glacier stages could be found in the upper sections of the Dogna, Raccolana and Bala valley. For the moraines of very low altitudes in the Resia valley, at the entrance to Možnica and the upper Raccolana valley pollen analyses are available. All considerations in the paper are estimations based on geomorphological and climatological experience.
Keywords: Italija; Italy; Alpe; Alps; poledenitev; pleistocen; relief; topography; morene